Associated Factors with Hypnobirthing Implementation in Trimester III Pregnant Women at Diana Panitra Clinic Medan in 2020 - Endryani Syafitri; Muthia Sari Mardha (STIKes Patria Husada Blitar, 2021)
Almost all maternal experienced anxiety and fear during pregnancy, labor, and after childbirth. One of the methods is used to reduce childbirth anxiety namely hypnobirthing. The purpose of this study was to determine the factors associated with the implementation of hypnobirthing in third trimester pregnant women at the Diana Panitra Clinic Medan in 2020. The design of this study used an analytic survey with a cross-sectional approach. The population of the study were all 30 third trimester pregnant women, and sample using accidental sampling techniques. The independent variables in this study are knowledge, husband's support, distance from facilities, and mother's interest. The instrument used a questionnaire. The data analysis technique used univariate and bivariate analyses. The results showed that there is a relationship implementation of hypnobirthing between knowledge with p-value (sig) = 0.044, husband's support with p-value (sig) = 0.004, facility distance and p-value (sig) = 0.019, and maternal interest with p-value (sig) = 0.015. The conclusion of this study is that there is a relationship between knowledge, husband's support, the distance of facilities, and mother's interest with the implementation of hypnobirthing in trimester III pregnant women at the Diana Panitra Clinic Medan in 2020. And it is hoped that health workers will participate in providing information about the benefits of hypnobirthing during pregnancy.